Opisthorchis felineus infection, risks, and morbidity in rural Western Siberia, Russian Federation - Fedorova, Olga S. (PLoS Negl Trop Dis, 2020)
BACKGROUND: The liver fluke, Opisthorchis felineus, is widely distributed throughout Europe and large parts of the Russian Federation. In Western Siberia, information about opisthorchiasis is lacking although infection may lead to severe liver and bile duct diseases. We aimed to assess the current prevalence of O. felineus infection along with associated risk factors and morbidity in rural Western Siberia. METHODS: We conducted a community-based, cross-sectional study in the rural Shegarskiy district, Tomsk Oblast, Russian Federation. All household members (≥ 7 years) present on the survey day were enrolled (n = 600). Two stool samples per person were examined for helminth eggs, using PARASEP (DiaSys Ltd, UK). The number of eggs per gram (EPG) of feces was recorded. Each study participant was interviewed to determine risk factors, using a pre-tested questionnaire. An abdominal ultrasonography examination of liver and bile ducts was performed with a mobile, high resolution ultrasound device. In total, 488 persons completed assessments (two stool samples, completed questionnaires); of those, 436 individuals had an ultrasonography (US) examination. RESULTS: We observed a prevalence of O. felineus infection of 60.2%. Significant risk factors for infection were the consumption of river fish (odds ratio from adjusted analysis [aOR] 2.4, 95% CI 1.52–3.95, p<0.001), particularly stock fish (OR from multivariable analysis [mOR] 3.2, 95% CI 2.63–3.80, p<0.001), smoked fish (mOR 1.5, 95% CI 1.24–1.72, p<0.001), frozen fish (mOR 1.6, 95% CI 1.29–2.02, p<0.001), and raw fish (mOR 1.4, 95% CI 1.05–1.84, p = 0.02); and fishing activities (mOR 1.2, 95% CI 1.03–1.43, p = 0.019). Women had a higher risk of infection than men. Infection was associated positively with age and negatively with socio-economic status. The respondents’ general awareness of opisthorchiasis was quite high (93.2%), but their knowledge about infection transmission and prevention was insufficient. Children aged 7–18 years old had a lower level of awareness compared to adults. The abdominal ultrasonography results demonstrated a strong association between O. felineus infection and gallbladder stones (mOR 2.8, 95% CI 1.33–6.04, p = 0.007) and periductal fibrosis of intrahepatic bile ducts (mOR 1.9, 95% CI 1.08–3.46, p = 0.026). CONCLUSION: O. felineus infection is highly prevalent in rural regions of Western Siberia, and associated with severe hepatobiliary pathology. Identified risk factors will be used to develop a comprehensive targeted O. felineus infection control program.